The use of Endo barrier for prevention of COVID‐19 infection enables upper gastrointestinal endoscopy with high patient satisfaction in private clinic - Atsushi Imagawa; Hideki Kobara; Noriko Nishiyama; Tsutomu Masaki (DEN Open)
Abstract Objectives In the midst of the coronavirus disease 2019 (COVID‐19) infection pandemic, practitioners who perform endoscopic examinations need to prevent infections through procedures, along with routine medical care. By using continuous suction, Endo barrier is thought to be effective in preventing the spread of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) droplets and aerosols. The study aimed to evaluate patient discomfort and satisfaction with the use of the Endo barrier during esophagogastroduodenoscopy (EGD). The study evaluated the system's effectiveness as well as the system's preparation time and the amount of burden on the medical staff. Methods EGD was performed on 788 consecutive cases using the Endo barrier. A questionnaire was used to survey patients after the procedure on four points: discomfort (feeling of pressure, breathlessness) and good points (feeling of relief and satisfaction) using a visual analog scale. In addition, patients were divided into two groups according to sedation status: with sedation (69.7%) and without sedation (30.3%), and their scores were compared. Additionally, the preparation time of the Endo barrier was measured. Results Patient discomfort was reported as minimal, resulting in a high level of satisfaction using this system. Although the overall results were better in the sedation group, the overall evaluation of the non‐sedated group was also favorable. Furthermore, preparation time (30 s) was less burdensome for medical staff. Conclusion The Endo barrier is an easy‐to‐implement tool to prevent COVID‐19 infection in private clinics, and both patients and staff were highly satisfied with the device with or without the use of sedation during EGD.